The Relationship Between Book Gradation and the Reading Interest of Visitors to Community Reading Centers in North Padang District, Padang City - Putri Rahminda; Lili Dasa Putri (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
The phenomenon of low public interest in reading is the driving force for this study. This issue is said to be partially caused by a mismatch between readers' capacities and the high level of book gradation. The community's lack of interest in reading in Community Reading Parks (TBM) is the driving force for this study. This issue is believed to be partially caused by the inappropriate grading of the accessible books. The objectives of this study are to: (1) describe the gradation of books available at TBM in North Padang District, Padang City; (2) describe the reading interests of TBM visitors in North Padang District, Padang City; and (3) ascertain the relationship between book gradation and reading interest of TBM visitors in North Padang District, Padang City. This study is a quantitative correlational investigation. 44 TBM visitors from Padang City's North Padang District made up the study population. Cluster random sampling was used to sample 33 individuals, or 75% of the population. The product-moment percentage formula was employed in the data analysis method. The study's findings show that: (1) the gradation of books available at TBM in Padang Utara District, Padang City is described as good; (2) the reading interest of TBM visitors in Padang Utara District, Padang City is still described as low; and (3) there is a significant negative relationship between book gradation and the reading interest of TBM visitors in Padang Utara District, Padang City. Based on the study's findings, the following recommendations can be made: (1) TBM institutions can enhance the quality of TBM services and facilities by implementing more systematic variations in book gradation, and they can serve as a guide for creating literacy programmes that are suitable for visitors' reading levels. (2) The National Library can increase the book collection by providing assistance to TBM for the completeness of book types and variations in book gradation that are appropriate to the level of reading ability of visitors. (3) Additional research on book gradation and guest reading interest in community reading parks can be developed for the same study. Keywords: Book Gradation, Reading Interest, Visitors, Community Reading Parks, Non-formal Education.